2016
DOI: 10.1515/aut-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Circular Woven Composite Preforms for Composite Pipes

Abstract: The main traditional technique for commercial manufacturing of composite pipes is filament winding in which the winding angle and the discontinuity of the structure (caused by starting and ending points of the winding process) are two important matters of concern. In the present study, circular woven fabric with its orthogonal net-shaped continuous structure was produced from polyester yarns. Fabric was wet with epoxy and hand lay-up was used to manufacture the composite pipes. Composite pipes were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(13 reference statements)
0
3
0
1
Order By: Relevance
“…Berkaitan dengan pemanfaatan komposit sebagai bahan pembentuk dari pipa diteliti oleh Ngafwan, dkk [15] menjelaskan bahwa temperatur berpengaruh terhadap kekuatan tarik dari pipa komposit dengan serat alami (batang pisang). Selain itu, pengamatan terhadap komposit dengan anyaman sebagai pembentuk dari pipa komposit diamati oleh Amid, dkk [16]. Hasil dari kajian dinyatakan bahwa posisi tegak lurus dari benang weft mempengaruhi tegangan lingkaran.…”
Section: Pendahuluanunclassified
“…Berkaitan dengan pemanfaatan komposit sebagai bahan pembentuk dari pipa diteliti oleh Ngafwan, dkk [15] menjelaskan bahwa temperatur berpengaruh terhadap kekuatan tarik dari pipa komposit dengan serat alami (batang pisang). Selain itu, pengamatan terhadap komposit dengan anyaman sebagai pembentuk dari pipa komposit diamati oleh Amid, dkk [16]. Hasil dari kajian dinyatakan bahwa posisi tegak lurus dari benang weft mempengaruhi tegangan lingkaran.…”
Section: Pendahuluanunclassified
“…Particularly in the last 20 years, fiber-reinforced plastics (FRP) have been used extensively as promising materials for resource-saving mobility. Due to their high stiffness at low mass compared to traditionally used materials, FRP are applied as load-bearing structures for the most dominant modes of transport, such as aviation, road, rail, or ship transport [1]. However, FRP can be used more efficiently and economically by integrating actuator materials for the realization of form variable structures.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that reorientation of the fiber tow by approximately 9.6% improves the stability and ductility of the seamless tubes. Amid et al 26 conducted hydrostatic burst testing on seamless fabric tubes and showed that increased burst strength is primarily attributed to the fabric architecture and alignment of fibers in the hoop direction. The burst pressure is the ultimate strength, and it is higher than the functional failure and first-ply-failure pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Seamless preforms have been recently introduced to address the failure mechanism of seam formation in FW and stitched laminated tubes. 17,2226 Hamada et al 22 showed that braided composite thick-walled tubes experience less delamination than laminated tubes. In their lateral compression tests, delamination propagation in multi-reciprocal tubes was shown to be impeded by through-thickness fiber bundles.…”
Section: Introductionmentioning
confidence: 99%